2015
DOI: 10.1186/s13012-015-0301-6
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of models and success factors for scaling up public health interventions

Abstract: BackgroundTo maximise the impact of public health research, research interventions found to be effective in improving health need to be scaled up and delivered on a population-wide basis. Theoretical frameworks and approaches are useful for describing and understanding how effective interventions are scaled up from small trials into broader policy and practice and can be used as a tool to facilitate effective scale-up. The purpose of this literature review was to synthesise evidence on scaling up public health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
333
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(353 citation statements)
references
References 41 publications
18
333
0
2
Order By: Relevance
“…However, it is clear from the literature and our research that, despite the unpredictable outcomes of scaling up attempts, a good plan can guide the scaling up process in the right direction and make success more likely. 2,3 Moreover, successful scale-up requires systematic use of evidence 2 , and it is particularly important that data from monitoring is linked to decision making throughout the scaling up process. This guide argues that plans for scaling up need to consider a broad range of factors and balance what is desirable with what is feasible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is clear from the literature and our research that, despite the unpredictable outcomes of scaling up attempts, a good plan can guide the scaling up process in the right direction and make success more likely. 2,3 Moreover, successful scale-up requires systematic use of evidence 2 , and it is particularly important that data from monitoring is linked to decision making throughout the scaling up process. This guide argues that plans for scaling up need to consider a broad range of factors and balance what is desirable with what is feasible.…”
Section: Resultsmentioning
confidence: 99%
“…1 They have been variously applied in the literature to describe the dissemination of a new technique, prototype product or process innovation; epidemiological and economic forecasting; 'growing' an organisational or system capacity to implement to a new level; and translating a small-scale initiative into a government policy. 2,3 For clarity, specific definitions for 'scalability' and 'scaling up' are needed. In the health sector, scalability is "… the ability of a health intervention shown to be efficacious on a small scale and or under controlled conditions to be expanded under real-world conditions to reach a greater proportion of the eligible population, while retaining effectiveness".…”
Section: Introductionmentioning
confidence: 99%
“…populations and the capacity to implement outreach and navigation components were trained to implement those program aspects [8]. The hub continued to deliver outreach and navigation in counties with limited capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the program expansion was highly successful: the number of women interested in receiving services greatly exceeded program expectations. That resulting rapid increase in demand had consequences that will require further study to help advance the science of scaling up and further rationalize models of preventive service delivery [8]. Previous studies have demonstrated that program designs able to accommodate flexibility during implementation can enhance service uptake among rural-residing women [7,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation